Analysis of the Influence Of Work Discipline and Leadership On the Performance of Employees of the Cooperative Tam Syariah KCP Tanjunganom Nganjuk - Angelina Kencana Putri; Mei Retno Adiwaty (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In an era of increasingly tight business competition every year, employee performance is a determining factor in the success of the TAM Syariah Cooperative as a company engaged in savings and loan services, this cooperative offers various models of savings and loan agreements according to customer needs. To improve employee performance, good human resources are needed. This study aims to analyze two important aspects of the performance of TAM Syariah Cooperative employees, namely the influence of work discipline and leadership on employee performance. The method used in this study is a quantitative method, with an analysis tool using SMART PLS. The population of this study consisted of 46 employees, and the entire population was also used as a research sample through a saturated sampling method. The findings of this study reveal that work discipline and leadership each have a positive and significant influence on employee performance, indicating that improvements in both factors can have a positive impact on productivity and work effectiveness in the company